2018
DOI: 10.1021/acs.langmuir.8b01183
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Surface Functionalities of Radio Frequency Magnetron-Sputtered ZnO Thin Films by Ar/NH3 Gas Mixture Surface-Wave Plasmas

Abstract: The surface functionalization of radio frequency magnetron-sputtered zinc oxide (ZnO) thin films tailored by low-pressure Ar/NH mixture surface-wave plasmas (SWPs) is discussed based on the results of photoluminescence (PL), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and spectrophotometric measurements. At an Ar/NH gas mixture ratio of 70%/30%, both the PL intensity of the near-band-edge emission and the XRD intensity of the ZnO(002) reflection peak were enhanced by about 5.5 and 8 times,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…19 Truscott and co-workers 37 also reported that NH radicals played a crucial role in the deposition of nitrogen-doped diamond by microwave plasma-activated CVD. Recently, Ciolan and co-workers 38 investigated Ar/NH 3 gas mixture plasma processing onto the RF magnetron-sputtered defective ZnO thin films. They claimed that the concentration of NH in the plasma was maximum at a small amount of NH 3 gas, which is determined from the product of NH 3 concentration and electron density.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…19 Truscott and co-workers 37 also reported that NH radicals played a crucial role in the deposition of nitrogen-doped diamond by microwave plasma-activated CVD. Recently, Ciolan and co-workers 38 investigated Ar/NH 3 gas mixture plasma processing onto the RF magnetron-sputtered defective ZnO thin films. They claimed that the concentration of NH in the plasma was maximum at a small amount of NH 3 gas, which is determined from the product of NH 3 concentration and electron density.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Second, it is controllable and reproducible, fast, and efficient even in moderate conditions, as it enables high energy levels, requires reasonable power, and maintains the sample close to room temperature, preventing the degradation of particles. [ 13,16–18 ]…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] On the other hand, some works explore zinc oxide functionalization through the plasma technique. [12][13][14][15] Plasma functionalization is an alternative to the traditional chemical methods, with several advantages. First, it is attractive from an environmental perspective since it is a dry, contaminant-free process.…”
mentioning
confidence: 99%
See 2 more Smart Citations